Kontribusi Pupuk Hayati dan Pupuk Anorganik untuk Meningkatkan Pertumbuhan dan Hasil Tanaman Padi Gogo pada Ultisols Jatinangor - Betty Natalie Fitriatin; Muthia Erwina Nabila; Tien Turmuktini; Emma Trinurani Sofyan; Anni Yuniarti (Soilrens, 2019)
Ultisols have low soil fertility problems. Beneficial microbes such as biofertilizers could improve soil fertility and the productivity of Ultisols sustainability.  The purpose of this research was to study the contribution of biofertilizers and NPK fertilizers to increase growth and yield of upland rice on Utisols. This experiment used a Randomized Block Design (RBD) in factorial pattern, consisting of  two factors with three replications. The first factor consisted of biofertilizer, which were ; without biofertilizer, biofertilizer consortia A (Pseudomonas mallei, P. cepaceae, Aspergillus niger and Penicillium sp., Azotobacter  chroococum, Azospirillum sp.) biofertilizer consortia B (Azotobacter choroococum, A. viilandii, Azospirillum, Pseudomonas cepaceae, Penicillium and Acitenobacter) and biofertizer consortia A+B. The second factor were NPK fertilizers with four levels ( 100%, 75%, 50% and 25% dosage of recomendation). The results showed that the application of  biofertilizer consortia increased growth of upland rice on Ultisols Jatinangor